Factors Affecting Students in the Kampung Bahasa Program at Public Vocational High School 1 of Boyolangu During Covid Pandemic - Renytasari, Fitria; Nurhadi, Didik; Marsono, Marsono (Fakultas Teknik Universitas Negeri Malang, 2022)
The Kampung Bahasa Program at vocational high schools are developed to get students used to English speaking at the school. Unfortunately, the number of students interested in joining the program decreased significantly during the pandemic. This research tried to identify main factors influencing students interest in the Kampung Bahasa Program at Public Vocational High School 1 of Boyolangu during covid pandemic. This was descriptive research using a qualitative approach. The data in this research were collected using some techniques including interviews, observation, and documentation. The data analyzed by interactive technique. The result of the research showed that internal factors affecting students in the Kampung Bahasa Program were the physiological factor which caused most students to be afraid of being infected with covid and the psychological factor that explained students’ need for English communication, on the one hand, and, on the other hand, their shyness in English communication. The external factors included familial support, socio-economic backgrounds of students’ family which allowed them to pay the tuition, the role of the English teacher of the tenth grade, and the fact that many fellow students joined the program. In addition, students’ interest in the program was also influenced by the socio-demographic factors.